THE IMPACT OF MODERNITY ON GENDER IN THE WORKPLACE IN INDIA - Diksha, (Trinity Law Review, 2025)
This research paper focuses on the impact of modernity on gender dynamics in  the Indian workplace. It explores the increasing participation of women in the  workforce, the evolving roles of men, the legal frameworks made to promote gender  equality, recent trends, and the challenges of discrimination and exploitation. By  analyzing the case laws and statistical data, this paper discusses the progress made to  achieve true gender equality in the workplace. This study also explores the impact of  technological advancements, the implications of corporate diversity initiatives, and  the importance of intersectionality in comprehending gender dynamics. Ultimately,  the paper advocates for comprehensive legal frameworks and corporate policies  that address both women’s and men’s experiences in the workplace, aiming to create  a more equitable and inclusive working environment. By focusing on the specific  context of the Indian workplace, this study adds to the larger conversation on gender  equality by concentrating on the particular setting of India and providing insights  into the advantages and disadvantages of modernity in influencing gender relations  in theworkplace.
Keywords: Modernity; workplace gender equality; discrimination; case laws; legal frameworks; Women’s Participation.